IMPLEMENTASI TEKNOLOGI PEMBESARAN IKAN BILEH (Rasbora sp.) BAGI PETANI IKAN DI KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Zulfadhli Zulfadhli; Rinawati Rinawati; Said Samsuli; Fazril Saputra; Mu’amar Abdan (Marine Kreatif, 2022)
The problem faced by partners is the need for more knowledge about the technique of raising bileh fish (Rasbora sp.) in aquaculture ponds. The bileh fish from nature does not last long in the fish farmer's pond. This is because the techniques used are not appropriate and inappropriate. The solution offered by the proposing team is assistance in the technique of enlarging bileh fish in cultivation containers. This activity is designed to provide knowledge and skills on bileh fish enlargement techniques. The service activities were carried out in Gampong Lhok seumot, Beutong District, Nagan Raya Regency, Aceh Province. The stages of implementation are 1). Preparation and arrangement of the program, 2). Program implementation, 3). Monitoring and evaluation, 4). Reporting and publication. The output of this service activity is the publication of scientific articles in accredited service journals and news in electronic mass media, increasing partner knowledge. The service results were obtained by increasing the knowledge and skills of fish farmers in raising bileh fish and increasing production (survival rate of bileh fish> 75%). Fish farmers continue to be assisted with the sustainability of the service activity program. Bileh fish, as a local fish, has the potential to be developed as a new candidate for aquaculture organisms.